COMMUNICATION ACTIVITIES OF EXTENSION WORKRES AND THEIR RELATION WITH THE APPLICATION OF WHEAT GROWERS TO AGRICULTURE RECOMMENDATIONS IN THE PROVINCE OF KIRKUK - Al-Salhi, A. T. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The relation between communication activities of extension agents and the applications of wheat growers to the wheat agricultural recommendations in Kirkuk, The main goal of this study was to determine it communications activities of extension agents correlated with the applications of wheat growers to wheat agricultural recommendations in the province of Kirkuk, Questionnaire was designed with to parts to achieve this study, The first part had (24) items related to communication activities (divided to four groups) and the second parts had eight item related to wheat agricultural recommendations stratified sample was used to drown the sample for 17 agriculture divisions in Kirkuk, The final sample had 150 growers from there divisions (18% of total 832), The result showed significant positive correlation (on 0.01 probability) between all communication activities and applications of wheat agricultural recommendations , in addition farmers need to improve their knowledge and skills in the area of soil management and agriculture method, All farmers need increase and give the attention and help them to build good relation whit research centers and authorities in the agriculture offices in order increase the production of wheat which is one of the best strategic crop.